The Role of Islamic Education in Shaping Tolerant and Inclusive Character in the Era of Globalization - Rizal Fathoni; Nurul Hudha Khoirul Arifin; Farhan Qomarudin (LP3M Pascasarjana STAI Ibnurusyd, 2025)
Globalization has a significant impact on the social, cultural, and religious dynamics of society, including the emergence of challenges of intolerance, exclusivism, and identity crises among the younger generation. In this context, Islamic education plays a strategic role in shaping the character of students who are tolerant, inclusive, and able to coexist harmoniously in a multicultural society. This article aims to analyze the role of Islamic education in building a tolerant and inclusive character in the era of globalization. This research uses a qualitative approach through library research by examining various scientific literature, educational policy documents, and relevant research findings related to Islamic education and character formation. The results of the study indicate that Islamic education plays a significant role in instilling the values ​​of religious moderation, such as tawassuṭ (balance), tasāmuh (tolerance), ta‘ādul (justice), and i‘tidāl (proportionality), which form the foundation for developing inclusive attitudes. The integration of these values ​​into the curriculum, dialogic learning methods, and the role models of educators have proven effective in developing awareness of diversity and mutual respect. Thus, Islamic education not only functions as a means of transferring religious knowledge, but also as a strategic instrument in shaping the character of students who are adaptive, open, and oriented towards global peace.